Serial, self-terminating search can be distinguished from others: Evidence from multi-target search data. - Lee, Jongmin; Jung, Koeun; Han, Suk Won (Cognition, 2021)
How do people find a target among multiple stimuli? The process of searching for a target among distractors has been a fundamental issue in human perception and cognition, evoking raging debates. Some researchers argued that search should be carried out by serially allocating focal attention to each item until the target is found. Others claimed that multiple stimuli, sharing a finite amount of processing resource, could be processed in parallel. This strict serial/parallel dichotomy in visual search has been challenged and many recent theories suggest that visual search tasks involve both serial and parallel processes. However, some search tasks should primarily depend on serial processing, while others would rely upon parallel processing to a greater extent. Here, by simple innovation of an experimental paradigm, we were able to identify a specific behavioral pattern associated with serial, self-terminating search and clarified which tasks depend on serial processing to a greater extent than others. Using this paradigm, we provide insights regarding under which condition the search becomes more serial or parallel. We also discuss several recent models of visual search that are capable of accommodating these findings and reconciling the extant controversy.